2021
DOI: 10.3390/life11111187
|View full text |Cite
|
Sign up to set email alerts
|

Target Nanoparticles against Pancreatic Cancer: Fewer Side Effects in Therapy

Abstract: Pancreatic cancer is the most common lethal tumor in America. This lethality is related to limited treatment options. Conventional treatments involve the non-specific use of chemotherapeutical agents such as 5-FU, capecitabine, gemcitabine, paclitaxel, cisplatin, oxaliplatin, or irinotecan, which produce several side effects. This review focuses on the use of targeted nanoparticles, such as metallic nanoparticles, polymeric nanoparticles, liposomes, micelles, and carbon nanotubes as an alternative to standard … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…It is being combined with other therapies such as gemcitabine and atezolizumab, in phase Ib/II clinical trials for the treatment of PC (NCT03193190). Additionally, studies are being conducted to investigate the use of NPs targeting the VEGF signaling pathway in cancer therapy, including PC (Ambasta et al, 2011;Roacho-Perez et al, 2021). TGF-β regulates various cellular, physiological and developmental processes as well as tissue homeostasis and repair.…”
Section: Targeting Of Growth Factors and Growth Factor Receptorsmentioning
confidence: 99%
“…It is being combined with other therapies such as gemcitabine and atezolizumab, in phase Ib/II clinical trials for the treatment of PC (NCT03193190). Additionally, studies are being conducted to investigate the use of NPs targeting the VEGF signaling pathway in cancer therapy, including PC (Ambasta et al, 2011;Roacho-Perez et al, 2021). TGF-β regulates various cellular, physiological and developmental processes as well as tissue homeostasis and repair.…”
Section: Targeting Of Growth Factors and Growth Factor Receptorsmentioning
confidence: 99%
“…The application of nanotechnology to the medical field, termed nanomedicine, [31][32][33] is enabling novel treatments to enter preclinical and clinical trials, with the aim of overcoming the limitations shown by conventional therapies: to mention but a few, light-and ultrasound-triggered minimally invasive techniques such as sonodynamic and photodynamic therapy have recently been applied to PDAC. [34,35] In addition to that, an ever-increasing knowledge of this particularly resistant tumor and its hallmarks has progressively led to the adoption of innovative and smart approaches: targeted therapies to avoid multidrug resistance and systemic toxicity, [36,37] stromal therapies aimed at a TME and vessel normalization, [38][39][40][41] the use of exosomes as nanocarriers for gene therapy. [42][43][44] Recent advances in nanotechnology are also allowing researchers to develop new platforms, namely nanoparticles, meant to improve drug delivery in the TME surrounding pancreatic cancer cells, while enhancing drug selectivity, providing bigger therapeutic windows, reducing side effects, and enabling real-time tracking abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional drug delivery systems, polymeric micelles have many merits such as the well-controlled size distribution, improved solubility, the enhanced permeability and retention (EPR) effect, good stability, and reduced toxicity ( Chowdhury and Singh, 2020 ; Majumder et al, 2020 ). In addition, drug-targeting at the lesion site can be achieved by introducing targeted functional groups on the surfaces of the amphiphilic polymers ( Roacho Perez et al, 2021 ). Amphiphilic polymers can load hydrophobic drugs through physical interaction or chemical bonding.…”
Section: Introductionmentioning
confidence: 99%